New glucose-lowering drugs in patients with heart failure - Plamen Gatzov (Българска кардиология, 2021)
The cardiovascular diseases are one of the main causes of mortality in the countries of Europe and North America. The heart failure (HF) and diabetes mellitus (DM) are widely spread diseases that become more frequent with the population aging in those regions. The algorithm of HF treatment in the last two decades includes several new medications. The SGLT-2 inhibitors (dapagliﬂ ozin, empagliﬂ ozin and canagloﬂ ozin) are new class anti diabetic medications which have positive effect on cardiovascular complications in patients with and without DB. The main trials using those medications in this group of patients and the most probable mechanisms, responsible for their effects, are the topic of this review.